2019
DOI: 10.1111/liv.14163
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic steatohepatitis is associated with a higher risk of advanced colorectal neoplasm

Abstract: Background & Aims Nonalcoholic fatty liver disease (NAFLD) is known to increase the risk of adenomatous colonic polyps. However, the role of screening colonoscopy in patients with biopsy‐proven NAFLD in detecting advanced colorectal neoplasm is not clearly evidence‐based. Therefore, we investigated whether the histological severity of NAFLD is associated with advanced colorectal neoplasm. Methods This study included patients ≥18 years old who underwent screening colonoscopy between 2013 and 2018 within a biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 37 publications
4
42
0
Order By: Relevance
“…NAFLD was associated with an increased polyp rate and HRS. These findings are in line with studies focusing on this specific subgroup of patients . The metabolic syndrome has already been linked to CRC and is closely associated with NAFLD .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…NAFLD was associated with an increased polyp rate and HRS. These findings are in line with studies focusing on this specific subgroup of patients . The metabolic syndrome has already been linked to CRC and is closely associated with NAFLD .…”
Section: Discussionsupporting
confidence: 86%
“…These findings are in line with studies focusing on this specific subgroup of patients. 5,13 The metabolic syndrome has already been linked to CRC 32 and is closely associated with NAFLD. 33 Thus, it is difficult to keep the two entities' effects on the colon apart.…”
Section: Liver Disease Etiologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed selection flow diagram of eligible literature is presented in Figure 1. A total 20 eligible studies that were included in the meta-analysis include 12 cross-sectional studies, [14][15][16][21][22][23][24][25][26][27][28][29] six cohort studies, [30][31][32][33][34][35] and two case-control studies. 36,37 The main characteristics of the included studies are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that active Helicobacter pylori infection (Hp-I) with concomitant nonalcoholic fatty liver disease (NAFLD), metabolic syndrome, might be involved in colorectal adenoma (CRA) to colorectal cancer (CRC) sequence. The recent study also reported an impact of Hp-I related metabolic syndrome on lower gastrointestinal tract oncogenesis 1. There is growing evidence for a potential association between Hp-I and NAFLD and malignancies 2.…”
mentioning
confidence: 94%